Bullying: a responsabilidade civil aquiliana dos estabelecimentos de ensino por danos morais no ambiente escolar - Lima, Camila Montenegro (2008)
Analyzes the juridical viability to be educational establishments responsible for extrapatrimonial damages resulting from school bullying, fact characterized for a set of cruel, intimidating and repetitive actions, by means of which a student is submitted by his mates to a condition of instability psychological. Presents the peculiarities of this specific form of violence, as well as inserts in the subject of moral damage the effects of related phenomenon on the victim. Discourses about pertinent extracontratual civil liability to the educational rendering of services, demarcating the legal regimen affection to the public and particular institutions of education. Emphasizes the relevance of the guard duty and monitoring on the student staff, obligation inherent one to the educational mission. Demonstrates some sustainable theses concerning the legitimacy to plead compensation for resultant moral damages of bullying in face of the education institution which competed watching over for the physical and emotional safety of educating attacked. Abording the possibility of the school to request a reimbursement for the aggressive pupil or his parents, it comes to support the damages caused for that one.